Combination of forecasts: A bibliography - Götz Trenkler; Butte Gotu (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 1998)
During the past thirty years, there has been considerable concern about combination of forecasts. Many of the articles and books dedicated to this specific area explain and demonstrate that combining multiple individual forecasts can improve forecast accuracy. The improvement in accuracy mainly depends on forecast combination techniques which range from simple combinations like averaging the forecasts to more complex ones that use the Bayesian approach. This paper provides a bibliography of selected articles and books related to the combination of forecasts in various disciplines and is intended to be a catalog for locating contributions in research areas focusing on the theory and applications of combining forecasts. The bibliography includes recent articles and is as up-to-date as possible.
Keywords: 519; Prognoseverfahren; Zeitreihenanalyse; Theorie